Mouse preantral follicle development in two-dimensional and three-dimensional culture systems after ovarian tissue vitrification. (November 2015) - Sadr, Seyedeh Zeynab; Ebrahimi, Bita; Shahhoseini, Maryam; Fatehi, Roya; Favaedi, Raha
Abstract: Objectives: This work on follicle culture and evaluation of expression of oocyte maturation genes helps to better understand the complicated processes of folliculogenesis and to develop new approaches for infertility treatment. Study design: Ovaries of 12-day-old female NMRI mice were divided into control and vitrification groups. After vitrification and warming procedures, ovarian tissue morphologies were histologically evaluated and compared to those of the control group. In the second stage, preantral follicles were mechanically isolated from non-vitrified and vitrified ovaries and cultured for 12 days in two-dimensional (2D) and three-dimensional (3D) systems. Finally, the survival and growth rate of follicles and quantitative expression of oocyte maturation genes ( Gdf9, Bmp15 and Bmp6 ) were studied. Result: Morphological integrity of ovarian tissue in vitrification group was well preserved. Survival rates of cultured preantral follicles in control group during 2D and 3D systems were somewhat similar, but were significantly different between 2D and 3D systems in vitrification group. Although the growth rate of follicles was similar in the 3D system in both groups, substantially higher growth rate was observed for the control group in the 2D system. Expressions of oocyte maturation genes were, to some extent, similar between control and vitrification groups. There was a remarkable reduction in expression pattern of genes in 3D compared to 2D system in both experimental groups, during the 12th day of culture period. Conclusions: 3D in-vitro culture system could be appeared more appropriate than 2D culture system for preservation of follicles in terms of spatial morphology, growth rate and expression reduction of maturation genes.